Integrasi Kepercayaan Digital dan Pengalaman Phygital dalam Pengalaman Pelanggan Omnichannel: Suatu Kajian Literatur Sistematis - Deny Ariyanto; Nur Afifah; Mustaruddin; Titik Rosnani (Universitas Muhammadiyah Pontianak, 2026)
This study systematically reviews the literature on omnichannel customer experience, digital trust, and phygital experience, which have become increasingly important in digital retail environments. The objective is to identify dominant themes, theoretical foundations, research trends, and future directions. Using the PRISMA protocol, 62 Scopus-indexed articles published between 2016 and 2025 were analyzed through thematic analysis. The findings indicate that customer experience remains the dominant theme, while digital trust and phygital experience are emerging research areas. The review highlights the growing role of AI and AR in omnichannel environments and provides insights for developing customer-centered strategies and future research agendas. Keywords: Omnichannel Customer Experience; Digital Trust; Phygital Experience; Customer Engagement; Channel Integration; Customer Loyalty